A reservoir-damage-free encapsulated acid dually controlled by hydrogen ion concentration and temperature. Issue 58 (21st October 2019) - Luo, Zhifeng; Zhang, Nanlin; Zhao, Liqiang; Wu, Lin; Liu, Pingli; Ren, Dengfeng; Qing, Chun
Abstract : Oil and gas exploration and development extends from medium-low temperatures to high and ultra-high temperatures with the development of the oil and gas industry. Abstract : Oil and gas exploration and development extends from medium-low temperatures to high and ultra-high temperatures with the development of the oil and gas industry. High-temperature deep carbonate reservoir acid fracturing has introduced more stringent requirements, a slower chemical reaction rate and excellent dissolution performance of acid systems, which means that the acid system should still have a certain dissolution ability above 135 °C. A novel water-soluble encapsulated acid (EA), dual controlled by hydrogen ion concentration and temperature, was developed to exploit ultra-high-temperature carbonate reservoirs. The encapsulating material was insoluble and isolated the internal solid acid at high H + ion concentrations and low temperatures, but the solid acid was released as the encapsulating material was dissolved at low H + ion concentrations and high temperatures. This unique performance was characterized by ESEM, TGA, FTIR, NMR, mechanical performance, solubility, etching performance, and etching fracture conductivity. All the scientific results show that this EA can be applied as a long-distance etching acid controlled by H + ion concentration and temperature, without the need for a thickener and emulsifier to reduce the reaction between the rock and the acid near the wellbore. The test results demonstrated that the solid acid had good thermal stability at 135 °C, the encapsulation material was almost insoluble in high acid concentrations (>14%) at any temperature, and the solid acid began to release when the concentration of hydrochloric acid was less than 14% and the temperature was higher than 95 °C. The rock etching and dissolution behavior was better than that of HCl with the same concentration and the etching fracture conductivity was improved by supplementing the consumption of H + ions when etching rock. The encapsulating material is completely dissolved after acid fracturing, avoiding reservoir damage by the residue. The described EA is a promising approach for application in acid fracturing of carbonate reservoirs at ultra-high temperature (>135 °C).